THE IMPACT OF BRAND IMAGE, BRAND TRUST AND BRAND AWARENESS ON AQUA LOYALTY BRAND - Silvia Hendrayanti; Ulan Terini (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract Aqua is a Bottled Drinking Water (AMDK) brand that has always been a Top Brand for 5 consecutive years, 2016 - 2019. However, in 2020 it only experienced an increase of 0.5% compared to newcomer products, which rose around 1.1% -1.8%. The purpose of this study was to determine the effect of brand image, brand trust and brand awareness on the brand loyalty of Aqua consumers at Ibu Sendangdawung Store. In this study, researchers used a non-probability sampling technique using a sample of 99 respondents. The data analysis technique used classical assumption test, multiple linear regression analysis, hypothesis test. From the results of data processing, the brand image has a significance value of 0.001 < 0.050. For the brand trust variable, the significance value is 0.047 < 0.050. And the brand awareness variable has a significance value of 0.040 < 0.050. All variables X1, X2, and X3 have a positive and significant effect on variable Y. It is hoped that Toko Ibu will increase brand trust by providing quality products and good service so that customers have a positive value for Aqua products because brand trust has the lowest regression coefficient among other variables.